(untitled) (Comprehensive Journal of Science, 2024)
This study aimed to develop a proposed framework that explains the impact of credit risk disclosure on the quality of financial reports, with the aim of meeting the requirements of users of financial reports. This was done by determining the value of the provision for loan losses, the percentage of non-performing loans, the liquidity ratio, capital adequacy, financial leverage, the size of the bank, and the extent to which these items affect the assessment of the bank’s efficiency and profitability. This is intended to reduce credit risk. The study was conducted on a sample of commercial banks in Libya, which included 10 commercial banks, and the study continued from 2019 to 2022. Data was collected through the financial statements of the concerned commercial banks. The necessary statistical analyzes were conducted to test the study hypotheses. The results of the study showed, through statistical analyzes of the data, that there is a fundamental impact of the disclosure of credit risks on the quality of financial reports.